Penerapan Budaya Positif Sekolah Melalui Program Sekolah Ramah Anak Di TK Negeri 23 Dodu - Asrarul Mufidah; Agus Salam; Syahru Ramadhan (JURNAL ARMADA PENDIDIKAN, 2025)
The background of this study is driven by the need to develop an educational approach that not only focuses on academic aspects but also on the formation of children's social and emotional character. The Child-Friendly School Program as implemented in TK Negeri 23 Dodu Kota Bima is expected to create an environment that is safe, inclusive and supports positive social interactions. This research uses a qualitative approach with a case study method, where data is collected through direct observation, interviews with teachers, parents, and children as well as analysis of school documentation related to the implementation of this program. The results showed that the implementation of the SRA Program at TK Negeri 23 Dodu was effective in shaping a positive culture among children. The program succeeds in creating a safe and comfortable school atmosphere, which allows children to develop better, both socially and emotionally. Teachers and staff play an important role as role models in teaching positive values, while a system of rewards and positive reinforcement increases children's motivation and self-confidence. In addition, collaboration between schools and parents strengthens the implementation of positive values both at school and at home. Overall, the implementation of this program succeeded in shaping children's better character, preparing them to face future social challenges.